Floating gated silicon-on-insulator nonvolatile memory devices with Au nanoparticles embedded in SiO1.3N insulators by digital sputtering method - Lee, Dong Uk; Lee, Min Seung; Kim, Jae-Hoon; Kim, Eun Kyu; Koo, Hyun-Mo; Cho, Won-Ju; Kim, Won Mok (AMER INST PHYSICS, 2007)
Floating gated silicon-on-insulator nonvolatile memory devices with Au nanoparticles embedded in SiO1.3N insulators were fabricated. The tunneling SiO1.3N insulator, Au nanoparticles, and control SiO1.3N insulator were sequentially deposited by digital sputtering method at 300 degrees C. The size of Au nanoparticles was controlled in the range of 1-5 nm by adjusting the deposition thickness of Au layer and the density of Au nanoparticles was approximately 1.5x10(12) cm(-2). A significant threshold voltage shift of fabricated floating gate memory devices was obtained due to the charging effects of Au particles and the memory window was larger than 2.5 V. (c) 2007 American Institute of Physics.
Keywords: OXIDE-SEMICONDUCTOR STRUCTURES; NANOCRYSTALS; FABRICATION